PEMBELAJARAN KONSEP DIRI UNTUK MENUMBUHKAN KETERAMPILAN SOSIAL ANAK USIA DINI: PEMBELAJARAN KONSEP DIRI UNTUK MENUMBUHKAN KETERAMPILAN SOSIAL ANAK USIA DINI - Oktavia, Yuki (PRODI PKAUD, IAKN TARUTUNG, 2022)
Abstract The purpose of this research is to find out how self-concept helps the development or social skills in early childhood. The method used in this research is literature review. After the data is collected from several sources, it is then processed and concluded. The results of the study are that self-concept is the result of the human learning process through relationships with other people and the environment has an important role in the process of knowing oneself, especially in the experience of relationships with other people and how other people treat themselves which will form social skills in children from an early age. Self-concept is the most important thing to establish a balanced relationship with peers. A balanced friendship relationship can be obtained if the child has self-confidence and can face various problems and find solutions. Social skills also make him easily accepted by other children because he is able to behave appropriately according to the expectations of his environment. Keyword: self-concept, social skills